A port industry solid waste-based goods yard pavement base material and a preparation method thereof

CN120757355BActive Publication Date: 2026-10-09SHANDONG HARBOR ENG GRP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510892128.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2026-10-09
Estimated Expiration
2045-06-30

AI Technical Summary

Technical Problem

[0005]针对现有的临港产业大宗固废材料无法合理利用的技术问题,本发明提供一种临港产业固废基货物堆场路面基层材料及其制备方法,以解决上述问题

Benefits of technology

本发明能够有效地利用临港产业园区的固废资源,减少固废堆砌造成的环境污染。本发明还能够有效地利用低价值固废进行绿色建材生产从而降低绿色建材生产成本。能够有效地减少碳排放量,助力临港产业绿色低碳经济的发展。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a kind of port industry solid waste based goods yard pavement base material and preparation method thereof, belong to the technical field of road engineering.The yard pavement base material is mainly composed of dredged silt, gravel, activated iron smelting slag, water, solid waste based cementitious material, cement.The present application also provides a kind of preparation method of yard pavement base material.The present application can effectively utilize the solid waste resources of port industry park, reduce the environmental pollution caused by solid waste stacking.The present application can also effectively utilize low-value solid waste for green building material production to reduce the production cost of green building material.Effectively reduce carbon emissions, help the development of port industry green low-carbon economy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of road engineering, specifically to a base course material for solid waste-based cargo storage yards in port industries and its preparation method. Background Technology

[0002] Port-adjacent industrial clusters (such as channel dredging, port construction, steel smelting, and shipbuilding) generate massive amounts of solid waste annually (e.g., steel slag, fly ash, marine dredging silt, waste concrete, etc.) due to large-scale industrial activities. Traditional landfilling or stockpiling poses problems of land occupation, environmental pollution, and resource waste. In recent years, more and more solid waste has been utilized for high-value purposes. However, due to the complex composition (containing salts, alkalis, heavy metals, etc.) and regional enrichment characteristics of port-adjacent solid waste, direct resource utilization faces technical bottlenecks. For example, salt corrosion and poor volume stability limit its application in building materials.

[0003] Port storage yards are the core areas for storing bulk cargo, containers, and other open-air goods within the port area, primarily responsible for cargo turnover and loading / unloading. Due to heavy loads, high-frequency vibrations, and salt spray corrosion, port storage yards require base materials with higher strength (≥6MPa), durability, and deformation resistance than general road base materials.

[0004] Existing technologies largely focus on the modification and application of single solid wastes. Research on the collaborative treatment of multi-source solid wastes in port areas and the adaptation of port yard base materials to meet both strength and environmental requirements are limited. There is an urgent need to develop low-cost pretreatment processes and stability control technologies to achieve deep integration of large-scale solid waste disposal and green infrastructure. Existing traditional sand and gravel base materials are costly and non-renewable. However, bulk solid waste materials from port industries (such as iron smelting slag and dredged sand) have lower crushing values ​​and higher wear resistance compared to traditional sand and gravel materials, making them superior as base materials for port yard construction at a lower cost. How to rationally utilize bulk solid waste materials from port industries is a pressing issue that needs to be addressed. Summary of the Invention

[0005] To address the technical problem of the inability to rationally utilize bulk solid waste materials in port-related industries, this invention provides a base course material for solid waste-based cargo storage yards in port-related industries and its preparation method, thereby solving the aforementioned problems.

[0006] The technical solution of this invention is as follows: In a first aspect, the present invention provides a base course material for a solid waste-based cargo storage yard in a port-adjacent industry. The base course material is mainly composed of dredged mud and sand, gravel, activated iron smelting slag, water, solid waste-based cementitious materials, and cement.

[0007] Furthermore, the base course material of the stockpile road surface comprises, by weight, the following components per cubic meter: 1000-1300 kg of dredged sludge, 200-500 kg of crushed stone, 700-1000 kg of activated iron smelting waste slag, 100-150 kg of water, 50-70 kg of solid waste-based cementitious material, 50-70 kg of cement I, and 10-20 kg of anti-expansion densifying agent. The solid waste-based cementitious material, by weight, comprises, per 100 kg: 5-20 kg of cement II, 10-20 kg of desulfurization ash, 5-20 kg of industrial by-product gypsum, 40-60 kg of cold-extraction slag, 10-20 kg of activated iron smelting waste slag powder, 0-2 kg of activator, and 1-2 kg of alkaline slag.

[0008] The iron smelting waste slag is soaked in seawater for 30 days and then screened. Waste slag with a particle size D90 of 5 mm to 30 mm is identified as activated iron smelting waste slag and used as coarse aggregate in the base course material of the stockpile road. Waste slag with a particle size D90 < 5 mm is dried at 100℃ for 6 hours and then mechanically ground to be used as iron smelting steel slag powder in solid waste-based cementitious materials. This invention utilizes the weak alkalinity of seawater to disrupt the complete solid solution on the surface of the iron smelting waste slag and reacts with free MgO and CaO, which affect the stability of the waste slag. Furthermore, tidal changes are used to erode the surface of the stockpiled iron smelting waste slag.

[0009] Furthermore, a grinding aid is added during mechanical grinding. The grinding aid is at least one of triethanolamine, polycarboxylate-based grinding aid, or triisopropanolamine. The grinding time is ≥70 min, and the specific surface area of ​​the iron smelting waste slag powder is ≥400 m². 2 / kg.

[0010] Furthermore, the dredged silt is a mixture of medium and fine sea sand, with a fineness modulus of 1.8 to 2.8, a mud content of <40%, a crushing value of <20%, and a mud lump content of <5%.

[0011] Furthermore, the crushed stone is granite gravel with a particle size of 10-30 mm and continuous gradation.

[0012] Furthermore, the iron smelting waste slag is a crushed stone material after iron smelting furnace slag is crushed and sorted, with a particle size of 10~25 mm and continuous gradation.

[0013] Furthermore, the water is tap water, reclaimed water, or seawater, with a salt content of <5%.

[0014] Furthermore, the alkali residue is chlor-alkali waste residue, wherein the alkali content in the alkali residue, calculated as sodium hydroxide, is not less than 40%.

[0015] Furthermore, the cement one and cement two are ordinary 42.5 silicate cement.

[0016] Furthermore, the activator is one or more of sodium sulfate, hydrated sodium silicate, sodium hydroxide, sodium carbonate, triethanolamine, triisopropanolamine, and sodium metabisulfite. The activator can enhance the mechanical strength of the solid waste agent cementitious material and adjust the setting time. The anti-expansion densifying agent is one or more of tailings, bentonite, fly ash, and silica fume. The anti-expansion densifying agent can, to a certain extent, densify the material structure, giving the material self-healing properties after expansion and cracking.

[0017] Secondly, the present invention provides a method for preparing the above-mentioned road base material, comprising the following steps: (1) Pretreatment of iron smelting waste slag Seawater immersion is used to accelerate the aging pretreatment of iron smelting waste slag. The waste slag is immersed in seawater at a water-to-solid volume ratio of 2:1. The weak alkalinity of seawater disrupts the complete solid solution on the surface of the waste slag and reacts with free MgO and CaO, which affect the stability of the waste slag. Tidal changes are used to erode the surface of the stockpiled waste slag. The pretreatment cycle for a single batch of waste slag is 20-30 days.

[0018] (2) Screen the eroded iron slag and retain the iron slag with a particle size of 5-30 mm for use as coarse aggregate in the base material of the stockpile road surface; retain the iron slag with a particle size of less than 5 mm, dry it at 100 ℃ for 6 hours, and then mechanically grind it to be used as iron slag powder in solid waste-based cementitious materials. The grinding time shall not be less than 70 min to ensure that the specific surface area of ​​the iron slag powder is not less than 400 m². 2 / kg. Grinding aids may be added during the grinding process, and the grinding aids may be at least one of triethanolamine, polycarboxylate-based grinding aids, or triisopropanolamine.

[0019] (3) Raw material metering and batching After weighing each component, it is transferred to a mixer and mixed evenly to obtain the road base material.

[0020] The beneficial effects of this invention are as follows: This invention effectively utilizes solid waste resources in the port industrial park, reducing environmental pollution caused by solid waste accumulation. It also effectively utilizes low-value solid waste for green building material production, thereby reducing production costs. Furthermore, it effectively reduces carbon emissions, contributing to the development of a green and low-carbon economy in the port industry. Detailed Implementation

[0021] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions in the embodiments of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.

[0022] Pretreatment of iron smelting waste slag Seawater immersion was used to accelerate the aging pretreatment of iron smelting waste slag. The waste slag was immersed in seawater at a water-to-solid volume ratio of 2:1, with a single pretreatment cycle of 30 days. After immersion treatment, the waste slag was baked. The treated waste slag was then screened, and waste slag with a particle size of 5 mm to 30 mm was retained for the preparation of the base course materials for the stockpile road surface in Examples 3 to 8. Waste slag with a particle size < 5 mm was retained for the preparation of Samples 1 to 4 in Example 1.

[0023] Example 1 Iron slag with a particle size of less than 5 mm was dried at 100℃ for 6 hours and then mechanically ground to obtain samples one through four.

[0024] (1) Sample 1: After baking, the iron slag was placed in a ball mill and 0.04% of the weight of the iron slag was added as a grinding aid. The grinding time was set to 70 min. After grinding, the specific surface area of ​​the iron slag was measured.

[0025] (2) Sample 2: After baking, the iron slag was placed in a ball mill and 0.04% of the mass of the iron slag (triethanolamine + triisopropanolamine, in a ratio of 1:1) was added as a grinding aid. The grinding time was set to 70 min. After grinding, the specific surface area of ​​the iron slag was measured.

[0026] (3) Sample 3: After baking, the iron slag was placed in a ball mill and 0.04% of the weight of the iron slag was added as a grinding aid. The grinding time was set to 70 min. After grinding, the specific surface area of ​​the iron slag was measured.

[0027] (4) Sample 4: After baking, the iron slag was placed in a ball mill and 0.04% of the mass of the iron slag was added as a grinding aid. The grinding time was set to 70 min. After grinding, the specific surface area of ​​the iron slag was measured.

[0028] The specific surface area of ​​samples one through four was measured, and the results are shown in Table 1 below: Table 1 - Specific Surface Area Test Results

[0029] Example 2 Preparation of solid waste-based cementitious materials Sample 1: Solid waste-based cementitious material contains the following components per 1000 kg by weight: 200 kg of cement 2, 100 kg of desulfurization ash, 90 kg of industrial by-product gypsum, 400 kg of cold extraction slag, and 190 kg of activated iron smelting waste slag powder (Sample 2 of Example 1). The alkaline slag and activator are mixed in a 1:1 ratio, with an admixture amount of 20 kg.

[0030] Sample 2: Solid waste-based cementitious material contains the following components per 1000 kg by weight: 200 kg of cement 2, 100 kg of desulfurization ash, 190 kg of industrial by-product gypsum, 400 kg of cold extraction slag, and 90 kg of activated iron smelting waste slag powder (Sample 2 of Example 1). The alkaline slag and activator are mixed in a 1:1 ratio, with an admixture dosage of 20 kg.

[0031] Sample 3: Solid waste-based cementitious material contains the following components per 1000 kg by weight: 200 kg of cement 2, 200 kg of desulfurization ash, 90 kg of industrial by-product gypsum, 400 kg of cold extraction slag, and 90 kg of activated iron smelting waste slag powder (Sample 2 of Example 1). The alkaline slag and activator are mixed in a 1:1 ratio, with an admixture dosage of 20 kg.

[0032] Sample 4: Solid waste-based cementitious material contains the following components per 1000 kg by weight: 200 kg of cement 2, 100 kg of desulfurization ash, 90 kg of industrial by-product gypsum, 500 kg of cold extraction slag, and 90 kg of activated iron smelting waste slag powder (Sample 2 of Example 1). The ratio of alkaline slag to activator is 1:1, and the dosage is 20 kg.

[0033] Sample 5: Solid waste-based cementitious material contains the following components per 1000 kg by weight: 100 kg of cement 2, 100 kg of desulfurization ash, 90 kg of industrial by-product gypsum, 600 kg of cold extraction slag, and 90 kg of activated iron smelting waste slag powder (Sample 2 of Example 1). The alkaline slag and activator are mixed in a 1:1 ratio, with a dosage of 20 kg.

[0034] Samples 1 through 5 were mixed thoroughly to obtain solid waste-based cementitious materials. The mechanical strength of the solid waste-based cementitious materials was evaluated according to GB / T17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)," and the setting time was evaluated according to GB / T1346-2011 "Test Method for Standard Consistency Water Requirement, Setting Time and Soundness of Cement." Specific test results are shown in Table 2. Table 2 - Test Results of Solid Waste-Based Cementitious Materials

[0035] Example 3 A method for preparing the above-mentioned road base material includes the following steps: The base course material for the stockpile road surface, per cubic meter by weight, contains the following components: 1100 kg of dredged sludge and sand, 800 kg of crushed stone, 400 kg of iron smelting slag, 120 kg of water, 60 kg of solid waste-based cementitious material (Example 2, Sample 4), 60 kg of cement, and 15 kg of anti-expansion densifying agent. After weighing using an electronic scale, the mixture is fed into a mixer, and the mixing time is controlled at 45 seconds. Once thoroughly mixed, the mixture is unloaded and transported to the construction site for application.

[0036] Example 4 A method for preparing the above-mentioned road base material includes the following steps: The base course material for the stockpile road surface, per cubic meter by weight, contains the following components: 1100 kg of dredged silt and sand, 600 kg of crushed stone, 600 kg of iron smelting slag, 120 kg of water, 60 kg of solid waste-based cementitious material (Example 2, Sample 4), 60 kg of cement, and 15 kg of anti-expansion densifying agent. After weighing using an electronic scale, the mixture is fed into a mixer, and the mixing time is controlled at 45 seconds. Once thoroughly mixed, the mixture is unloaded and transported to the construction site for application.

[0037] Example 5 A method for preparing the above-mentioned road base material includes the following steps: The base course material for the stockpile road surface, per cubic meter by weight, contains the following components: 1100 kg of dredged silt and sand, 400 kg of crushed stone, 800 kg of iron smelting slag, 120 kg of water, 60 kg of solid waste-based cementitious material (Example 2, Sample 4), 60 kg of cement, and 15 kg of anti-expansion densifying agent. After weighing using an electronic scale, the mixture is fed into a mixer, and the mixing time is controlled at 45 seconds. Once thoroughly mixed, the mixture is unloaded and transported to the construction site for application.

[0038] Example 6 A method for preparing the above-mentioned road base material includes the following steps: The base course material for the stockpile road surface, per cubic meter by weight, contains the following components: 1100 kg of dredged silt and sand, 200 kg of crushed stone, 1000 kg of iron smelting slag, 120 kg of water, 60 kg of solid waste-based cementitious material (Example 2, Sample 4), 60 kg of cement, and 15 kg of anti-expansion densifying agent. After weighing using an electronic scale, the mixture is fed into a mixer, and the mixing time is controlled at 45 seconds. Once thoroughly mixed, the mixture is unloaded and transported to the construction site for application.

[0039] Example 7 A method for preparing the above-mentioned road base material includes the following steps: The base course material for the stockpile road surface, per cubic meter by weight, contains the following components: 1100 kg of dredged sludge, 1200 kg of iron smelting slag, 120 kg of water, 60 kg of solid waste-based cementitious material (Example 2, Sample 4), 60 kg of cement, and 15 kg of anti-expansion densifying agent. After weighing using an electronic scale, the mixture is fed into a mixer, and the mixing time is controlled at 45 seconds. Once thoroughly mixed, the mixture is unloaded and transported to the construction site for application.

[0040] Example 8 A method for preparing the above-mentioned road base material includes the following steps: The base course material for the stockpile road surface, per cubic meter by weight, contains the following components: 1100 kg of dredged silt and sand, 400 kg of crushed stone, 800 kg of iron smelting slag, 120 kg of water, 80 kg of solid waste-based cementitious material (Example 2, Sample 4), 40 kg of cement, and 15 kg of anti-expansion densifying agent. After weighing using an electronic scale, the mixture is fed into a mixer, and the mixing time is controlled at 45 seconds. Once thoroughly mixed, the mixture is unloaded and transported to the construction site for application.

[0041] Test case In accordance with the requirements of the standards "JTG 3441-2024 Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" and "JTG / T F20-2015 Technical Specifications for Construction of Highway Pavement Base Course", the pavement base course materials prepared in Examples 3-8 were sampled twice at the construction site. The average values ​​of the experimental results are shown in Table 3 below: Table 3 - Test Results of Road Base Materials

[0042] Although the present invention has been described in detail by way of preferred embodiments, the present invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention.

Claims

1. A base course material for solid waste-based cargo storage yards in port-adjacent industries, characterized in that, The base material of the stockpile road surface mainly consists of dredged silt, crushed stone, activated iron smelting slag, water, solid waste-based cementitious material, and cement. Each cubic meter of the base material comprises the following components by weight: 1000-1300 kg of dredged silt, 200-500 kg of crushed stone, 700-1000 kg of activated iron smelting slag, 100-150 kg of water, 50-70 kg of solid waste-based cementitious material, 50-70 kg of cement, and 10-20 kg of anti-expansion densifying agent. Each 100 kg of solid waste-based cementitious material contains the following components by weight: 5-20 kg of cement, 10-20 kg of desulfurization ash, 5-20 kg of industrial by-product gypsum, 40-60 kg of cold-extraction slag, 10-20 kg of activated iron smelting slag powder, 0-2 kg of activator, and 1-2 kg of alkali slag. Among them, the iron smelting waste slag is soaked in seawater for 30 days and then screened. The iron smelting waste slag with a particle size D90=5 mm~30 mm is activated iron smelting waste slag and is used as coarse aggregate in the base material of the road surface of the stockpile. The iron smelting waste slag with a particle size D90<5 mm is dried at 100 ℃ for 6 hours and then mechanically ground to be used as activated iron smelting waste slag powder in solid waste-based cementitious materials.

2. The base course material for a port-adjacent industrial solid waste-based cargo storage yard as described in claim 1, characterized in that, During mechanical grinding, a grinding aid is added. The grinding aid is at least one of triethanolamine, polycarboxylate-based grinding aid, or triisopropanolamine. The grinding time is ≥70 min, and the specific surface area of ​​the activated iron smelting waste slag powder is ≥400 m². 2 / kg.

3. The base course material for a port-adjacent industrial solid waste-based cargo storage yard as described in claim 1, characterized in that, The dredged silt is a mixture of medium and fine sea sand, with a fineness modulus of 1.8 to 2.8, a mud content of <40%, a crushing value of <20%, and a mud lump content of <5%.

4. The base course material for a port-adjacent industrial solid waste-based cargo storage yard as described in claim 1, characterized in that, The crushed stone is made of granite with a particle size of 10-30 mm and a continuous gradation.

5. A base course material for a port-adjacent industrial solid waste-based cargo storage yard as described in claim 1, characterized in that, The activated iron smelting waste slag is a crushed stone-like material after iron smelting slag is crushed and sorted, with a particle size of 10~25 mm and continuous gradation.

6. The base course material for a port-adjacent industrial solid waste-based cargo storage yard as described in claim 1, characterized in that, The water is tap water, reclaimed water, or seawater, with a salt content of <5%.

7. A base course material for a port-adjacent industrial solid waste-based cargo storage yard as described in claim 1, characterized in that, The alkaline residue is chlor-alkali waste residue, wherein the alkaline content in the alkaline residue, calculated as sodium hydroxide, is not less than 40%.

8. The base course material for a port-adjacent industrial solid waste-based cargo storage yard as described in claim 1, characterized in that, The activator is one or more of sodium sulfate, hydrated sodium silicate, sodium hydroxide, sodium carbonate, triethanolamine, triisopropanolamine, and sodium metabisulfite. The activator can activate the mechanical strength of the solid waste agent cementitious material and adjust the setting time. The anti-expansion densifying agent is one or more of tailings, bentonite, fly ash, and silica fume.

9. A method for preparing a road base material as described in claim 1, characterized in that, Includes the following steps: (1) Pretreatment of iron smelting waste slag Seawater immersion is used to accelerate the aging pretreatment of iron smelting waste slag. The iron smelting waste slag is immersed in seawater at a water-to-solid volume ratio of 2:1, and the single pretreatment cycle of iron smelting waste slag is 30 days. (2) Screen the eroded iron slag and retain the iron slag with a particle size of D90 = 5~30 mm for use as coarse aggregate in the base material of the road surface of the stockpile; retain the iron slag with a particle size of D90 < 5 mm, dry it at 100 ℃ for 6 hours, and then mechanically grind it to be used as activated iron slag powder in solid waste-based cementitious materials; the grinding time shall not be less than 70 min, and the specific surface area of ​​the iron slag powder shall not be less than 400 m². 2 / kg; (3) Raw material metering and batching After weighing each component, it is transferred to a mixer and mixed evenly to obtain the road base material.

Citation Information

Patent Citations

  • Multi-source solid waste-based grouting cementing material as well as preparation method and application thereof

    CN111689752A

  • Low-carbon concrete as well as preparation method and application thereof

    CN114538844A

  • Cementing material based on metallurgical solid waste residues, preparation method and mortar mixture

    CN118307222A